1997
DOI: 10.4319/lo.1997.42.4.0769
|View full text |Cite
|
Sign up to set email alerts
|

Noeffects of ambient UV radiation detected in periphyton and grazers

Abstract: The vulnerability of periphyton and grazers to current and future levels of ultraviolet radiation (UV) has important ramifications for energy flow in shallow waters. We reduced ambient UV levels in a Tennessee stream with UV‐opaque Plexiglas suspended over the stream and compared periphyton under these Plexiglas filters to periphyton under UV‐transparent polyvinylidene film. The experiments were performed three times, from autumn 1993 to summer 1994. The last experiment included a treatment with reduced snail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 19 publications
4
31
2
1
Order By: Relevance
“…These findings are in agreement with previous studies on benthic diatoms from marine (e.g., Hillebrand et al 2000), and freshwater (Steinman 1996;Hill et al 1997), habitats. In our study, the absence of grazers generally favoured the abundance of the diatom genus Cocconeis.…”
Section: Grazing Effectssupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are in agreement with previous studies on benthic diatoms from marine (e.g., Hillebrand et al 2000), and freshwater (Steinman 1996;Hill et al 1997), habitats. In our study, the absence of grazers generally favoured the abundance of the diatom genus Cocconeis.…”
Section: Grazing Effectssupporting
confidence: 83%
“…Thus, any UV effects on benthic diatoms should most likely be found here (particularly in the intertidal). However, the lack of UV effects found on biomass and abundance of benthic Antarctic diatoms confirmed former studies at different geographical sites (e.g., Hill et al 1997). Earlier field-studies on UV effects on benthic microalgae have mainly focussed on soft bottom communities where benthic diatoms seem to be very tolerant to UV-B radiation (Peletier 1996; and references therein).…”
Section: Uv Effectssupporting
confidence: 62%
See 1 more Smart Citation
“…5 DISCUSSION Several investigations of the effects of UV radiation by exclusion of ambient UV observed reduced chl a accrual within +UV treatments in lakes Leavit 1996, Francoeur andLowe 1998) and artificial streams (Bothwell et al 1994, Hodoki 2005. In contrast, other studies conducted in lakes (Higley et al 2001, Watkins et al 2001), a wetland (Kahn and Wetzel 1999), and a stream (Hill et al 1997) found no significant differences in periphytic algal biomass between fill ambient sunlight (+UV) and PAR-only (-UV) treatments. In the present study, algal biomass appeared to be unaffected by W exposure.…”
Section: Resultsmentioning
confidence: 72%
“…Prior studies have observed reductions in algal photosynthesis and biomass accumulation in freshwater periphyton under full ambient light (+UV) as compared to -UV treatments (e.g., Vinebrooke and Leavitt 1996), whereas other studies have observed no affect of UV radiation (Hill et al 1997, Hodoki 2005. Shifts in algal species composition have also been observed in longer-term studies, with sensitivity to UV varying by taxon (Bothwell et al 1993, Vinebrooke and Leavitt 1996, Francoeur and Lowe 1998, Higley et al 2001).…”
Section: Introductionmentioning
confidence: 75%